Do religious programs in prison work? A quasi-experimental evaluation in the Israeli prison service - Haviv, Noam (Journal of experimental criminology, 2020)
Objectives Despite the prevalence of religious-oriented rehabilitation programs, few studies have assessed the effects of these programs on recidivism. Prior studies have generally focused on Christian-based programs in the USA and also suffer from a range of methodological problems, making it difficult to draw sound conclusions. The current study evaluates the effects of two Jewish-based programs in Israel. Methodology Using data provided by the Israeli Prison Services, propensity score matching was used to examine the effects of two religious-oriented rehabilitation programs on recidivism. A sub-sample of prisoners who progressed from the less intensive to the more intensive program was used as a proxy for examining the role of motivation and commitment. Findings Compared to non-participants, only those who participated in both programs had a significantly lower risk of recidivism. This sub-sample also had significantly lower recidivism than those who participated in only the less intensive of the two programs. Comparing participants of the two programs, those from the more intensive program had significantly more positive recidivism outcomes than those from the less intensive program. Conclusions The theoretical foundations of religious-oriented programs are that causing changes in levels of religiosity can lead to less recidivism. While prior studies have had difficulties in assessing the motivation to change of program participants, our findings provide evidence to support these theoretical underpinnings. That is, when religious-oriented programs succeed in engendering legitimate changes in levels of religiosity, they can have a positive effect on reducing recidivism.